Quantitative Approach to Single-Nucleotide Polymorphism Analysis Using MALDI-TOF Mass Spectrometry - Philip Ross; Laura Hall; Lawrence A. Haff (BioTechniques, 2000)
Pooling of DNA samples before genotyping is a valuable means of streamlining large-scale genotyping efforts in disease association studies, single-nucleotide polymorphism (SNP) validation or mutant allele screening programs. In this report, we explore the application of matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) to quantitative analysis of SNPs. The measurements are based on MALDI-TOF MS analysis of primer extension assays performed on standard mixtures of pooled PCR products at several test loci. The inherent high molecular weight resolution of MALDI-TOF MS conveys high specificity and good signal-to-noise ratio for performing accurate quantitation. The methods described maximize the sensitivity and quantitative capacity of MALDI-TOF MS while preserving the throughput and economic advantages of the MALDI-TOF platform. Using the format described, we demonstrate that allele frequencies as low as 5% can be detected quantitatively and unambiguously.